Pengelolaan Sampah Berbasis Masyarakat - Yunita Ismail (President University, 2019)
Community-based waste management is an effort to reduce and manage waste. The community, where the household is a part of it as one of the waste producers can reduce and reuse their waste and even provide an additional income. To make the community plays an active and continuous role in a waste management, an organization with community members is needed to run the management and utilize waste together, which will provide mutual benefits. From the community service activities that have been carried out, the community gives a positive response on managing waste. Institutions are needed to be made to maintain the sustainability of the waste management. Waste management activities are given to the parties who are homeowners, those who have an elementary education and those who are in a productive age (31-40 years).